2014
DOI: 10.1097/ta.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Blood component transfusion increases the risk of death in children with traumatic brain injury

Abstract: Epidemiologic study, level III. Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
2
22
0
2
Order By: Relevance
“…R ed blood cell (RBC) transfusion in critically ill patients is known to be associated with increased risks of nosocomial infection, suggesting a relationship between RBC transfusion and impaired host defense, although a causal link between RBC transfusion and immune function has not been clearly established. [1][2][3][4][5][6][7] Acquired suppression of innate (e.g., monocyte) and adaptive (e.g., lymphocyte) immune function are increasingly recognized as complications of critical illness and are independently associated with increased risks of adverse outcomes. [8][9][10][11][12][13] Immune function in the intensive care unit (ICU) can be measured by quantifying the ability of immune cells to produce cytokines in response to ex vivo stimulation.…”
mentioning
confidence: 99%
“…R ed blood cell (RBC) transfusion in critically ill patients is known to be associated with increased risks of nosocomial infection, suggesting a relationship between RBC transfusion and impaired host defense, although a causal link between RBC transfusion and immune function has not been clearly established. [1][2][3][4][5][6][7] Acquired suppression of innate (e.g., monocyte) and adaptive (e.g., lymphocyte) immune function are increasingly recognized as complications of critical illness and are independently associated with increased risks of adverse outcomes. [8][9][10][11][12][13] Immune function in the intensive care unit (ICU) can be measured by quantifying the ability of immune cells to produce cytokines in response to ex vivo stimulation.…”
mentioning
confidence: 99%
“…Bu tezi destekler şekilde travmatik beyin hasarlı hastalarda eritrosit transfüzyonunun mortaliteyi arttırdığı gösterilmiştir. 11 Rouette ve ark.…”
Section: Discussionunclassified
“…Hastaların eritrosit transfüzyonu sırasında bir hastada ateş olması dışında transfüzyonla ilgili bir yan etki gözlenmedi. 11 travmatik beyin hasarı olan çocuklarda bizim çalışmamızdaki sonuca benzer olarak mortaliteyi etkilemeyen hemoglobin eşik değeri olarak 8,0 g/dL sonucunu bulmuşlardır. Daha düşük hemoglobin düzeyi değerlerinde eritrosit transfüzyonu yapılması hastaları transfüzyonun yol açacağı olumsuz etkilerden koruyacaktır.…”
Section: Bulgularunclassified
“…The threshold for RBC transfusion in patients with TBI is controversial, and the optimal transfusion trigger is unknown [9]. In a recent retrospective review of 635 patients with isolated, severe TBI (Glasgow Coma Scale 3–8), the association between Hb levels and mortality was assessed [10].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…A recent retrospective study reviewed outcomes in 1607 pediatric patients with TBI, of which 178 received RBC transfusion [9]. The authors demonstrated that RBC transfusions in these patients were associated with poor outcomes and increased mortality.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%